Pengaruh Persepsi Siswa Tentang Profesionalisme GuruDan Intensitas Komunikasi Guru Dengan Siswa Terhadap Prestasi Belajar Ips Siswa Kelas Viii Smp Muhammadiyah 1 Kartasura Tahun Ajaran 2015/2016 - Bio, Rifky Aldino, Drs. Sudarto, HS. MM (2016)
INFLUENCE PERCEPTION OF STUDENT TEACHER PROFESSIONALISM AND INTENSITY OF COMMUNICATION TEACHER WITH STUDENT ACHIEVEMENT IPS CLASS VIII SMP MUHAMMADIYAH 1 KARTASURA 2015/2016 ACADEMIC YEAR Rifky Aldino Bio 210 110 175. Accounting Education Program. The Faculty of Education, University of Muhammadiyah Surakarta. 2016. The purpose of this study was to determine the effect of students' perception of the professionalism of teachers and intensity of communication teachers and students on the learning achievement IPS. This research is quantitative research with descriptive approach that examine the relationship between variables. The study population was all students of class VIII SMP Muhammadiyah 1 Kartasura the academic year 2015/2016, amounting to 132 students. Samples taken as many as 95 students. The sampling technique using proportional random sampling by means of a lottery. The data collection technique using a questionnaire that had been tested in advance and tested for validity and reliability test. Data analysis technique used is multiple regression analysis, t-test, F, R2 test, as well as the relative contribution and effective. The results showed that the regression equation is Y = 61.303 + 1,028.X1 + 0,968.X2. The equation shows that the level of students' perceptions of professional teachers and intensity of communication between teachers and students dngan. And research results menytakan that: (1) Perceptions of students on teacher professionalism positive effect on learning achievement IPS. Contributions of students' perceptions about the professionalism of the teacher to the student achievement IPS economy amounted to 45.1%; (2) The intensity of teacherstudent communication positive effect on learning achievement IPS. Contributions intensity of teacher-student communication to the student achievement IPS economy is 15.2%; (3) Perceptions of students about the professionalism of teachers and teacher-student communication intensity jointly positive effect on learning achievement in social studies class VIII student Muhammadiyah 1 Kartasura the academic year 2015/2016. Overall variables influence students' perceptions about the professionalism of teachers and teacher-student communication intensity accounted for 60.3% and the rest is affected by other factors that can not investigate. Keywords: teacher professionalism, intensity teacher communication with students, academic achievement IPS